1999
DOI: 10.1159/000057440
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Total Parathyroidectomy without Autotransplantation in Patients with and without Renal Failure

Abstract: The optimal surgical procedure for severe renal secondary hyperparathyroidism (sHPT) is still a point of controversy. Total parathyroidectomy (PTX) without auto-transplantation was abandoned for fear of an adynamic bone condition; however, in the case of autotransplantation recurrent sHPT is frequent and promotes atherosclerosis. We studied 11 hemodialysis patients (age 59±12 years) on dialysis for 18 (12–30) years in whom total PTX was performed due to severe sHPT (group I; intact PTH: 1,240±230 pg/ml), and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 37 publications
3
53
0
4
Order By: Relevance
“…Persistent or transient hypoparathyroidism, a condition feared because of the associated risk of adynamic bone disease, was observed in up to 68.3% of the patients during prolonged follow-up. Hampi et al [22], however, reported that even 20 years after total PTX without autograft a normal bone metabolism could be maintained in haemodialysis patients by adequate substitution with oral calcium and vitamin D despite almost undetectable PTH levels. This observation needs confirmation in the setting of renal transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Persistent or transient hypoparathyroidism, a condition feared because of the associated risk of adynamic bone disease, was observed in up to 68.3% of the patients during prolonged follow-up. Hampi et al [22], however, reported that even 20 years after total PTX without autograft a normal bone metabolism could be maintained in haemodialysis patients by adequate substitution with oral calcium and vitamin D despite almost undetectable PTH levels. This observation needs confirmation in the setting of renal transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Although there is some fear of adynamic bone disease in case of hypoparathyroidism and some resistance to constantly supplementing patients with active vitamin D postoperatively, tPTX without autotransplantation has found more followers during the last 5 years [22,23,24]. The procedure had already been suggested in the late 1980s and 1990s [6, 19,25,26,27,28]. In these centers, tPTX without autotransplantation (and mostly also without routine thymectomy) has been proven a useful and in the short and mid-term an easily manageable operative approach for end-stage renal failure patients with severe sHPT.…”
Section: Discussionmentioning
confidence: 99%
“…If an aluminum overload of the bone is excluded prior to PTX, the risk for low-turnover osteopathy after PTX is low. In a prospective study with protocol bone biopsies, no adynamic bone disease could be seen after tPTX alone [28]. On the other hand, adynamic bone disease is not exclusively associated with low PTH but also with a variety of other conditions such as aluminum overload, malnutrition, inflammation, osteoporosis and β 2 -microglobulin [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the expanding medical armamentarium to treat SHPT, PTX remains a valuable treatment option, especially in those patients who are refractory to medical treatment or cannot afford the expensive drugs [3]. Overall, parameters of mineral metabolism change favorably after a successful PTX [4,5,6]. Hypocalcemia, however, remains a frequently encountered complication and its prevention represents a clinical challenge as pronounced hypocalcemia is not without risks.…”
Section: Introductionmentioning
confidence: 99%